Characterization of cellulose fibers in Thespesia populnea barks: Influence of alkali treatment. (1st August 2019) - Kathirselvam, M.; Kumaravel, A.; Arthanarieswaran, V.P.; Saravanakumar, S.S.
Highlights: Thespesia populnea fibers treated at 5% NaOH for 60 min gives optimal results. Cellulose crystallinity of treated fibers increases from 48.17%–67.52%. Optimally treated fibers are thermally stable up to 341.82 °C. The consistency of tensile test results is validated with Weibull distribution model. SEM & AFM analysis reveals that fiber surface turns rough after alkali treatment. Abstract: Natural fibers are emerging as best alternatives for synthetic materials in selective applications. These fibers may not have the required properties in its raw form and hence needs some alterations in its characteristics. Likely, this article reports enhancement in surface and structural properties of Thespesia populnea bark fiber treated with NaOH under various concentration and soaking period. Fibers treated with 5% NaOH for 60 min yields noteworthy mechanical strength (678.41 ± 48.91 MPa) owing to its relatively high cellulose fraction (76.42%). Fourier transform infrared spectra endorses the removal of non-cellulosic compounds and X-ray diffraction studies reveals 13.6% growth in the size of cellulose crystals on optimally treated fibers. Weibull distribution model statistically interprets the reliability of acquired tensile test results. Finally, microscopic examinations with scanning electron microscopy and atomic force microscopy explore that fiber surface turns rough after alkali treatment and makes it appropriate for reinforcement in polymer matrices.